Oral language and the psychological processes of writing in a group of students with and without lead poisoning in Callao - Meléndez J., Magali (2015)
This study was carried in three schools. Its purpose was to investigate whether there were significant differences between two groups of students of the third grade of primary school in the Callao Region; regarding the development of the components of oral language andthe psychological processes involved in writing. The first group was characterized by the presence of lead poisoning and its attending schools located in the Lead Area. The second group showed no lead poisoning and studied in a school outside the lead-polluted area;although still within the Callao Region. The results showed differences between the two groups in the development of the components of oral language; especially in the syntactic and the semantic components. The group without poisoning showed better results than the other; however. Furthermore; the results of the study of the processes involved in writing showed slight differences in favour of the group with no lead poisoning; but they were not statistically significant. These regarded primarily the process of planning.